Oxygen condensation in ZIF-8 upon 'gate opening' structural transition. (17th November 2019) - Boada, Roberto; Diaz-Moreno, Sofia; Norman, Sarah E.; Bowron, Daniel T.
Abstract : We report a wide Q-range neutron diffraction study on the absorption of oxygen molecules into deuterated ZIF-8 as the system is taken through its gate-opening transition by applying gas pressure at 85 K. The combination of the quantitative nature of the total neutron scattering technique and the modelling performed using the Empirical Potential Structure Refinement (EPSR) technique has allowed us to determine the behaviour of the absorbed fluid upon condensation within the pores with unprecedented detail. The results show that the number of oxygen molecules found inside the central core of the spherical pore of the sodalite cage does not vary as the gate-opening transition is induced. After going through the structural transition, there is a rearrangement of the molecules and the extra molecules entering the structure are instead pushed towards the window apertures in the open structure. These results help to provide a greater insight into the nature of the structural flexibility of ZIF-8 and to understand its gas sorption behaviour. GRAPHICAL ABSTRACT: